Co(II)-TiO2/Ti Thin Film as Antibacterial Photocatalysts Escherichia Coli Under Visible Light Ilumination - Aritonang, Anthoni Batahan; Rozaqina, Nuri; Harlia, H. (BERKALA SAINSTEK, 2023)
A thin layer of TiO2 doped with Cobalt (II) immobilized on the surface of a titanium foil (Co(II)-TiO2/Ti) has been synthesized from a titanium foil (Ti) as a TiO2 precursor as well as a thin layer matrix and CoCl2.6H2O as a source of Co(II) on variations of 0.5%, 1% and 2%. Synthesis was carried out by anodizing method using ethylene glycol electrolyte solution with the addition of NH4F and followed by calcination treatment at 450ºC for 3 hours. The obtained Co(II)-TiO2 /Ti thin films were characterized using Fourier-transform infrared (FT-IR) spectroscopy, Diffuse Reflectance UV-Vis (DRSUV-Vis) and X-ray diffraction (XRD) methods. Doping Co(II) variations of 0.5%, 1.0% dan 2.0% in the TiO2 structure causes a shift in the vibrational absorption peak of Ti-O (460.99 cm-1) towards a smaller wave number of 459.06 cm-1 respectively ; 453.27 cm-1 and 451.34 cm-1. This is supported by the results of the DRUV-Vis analysis using the tauc plot method, which shows a decrease in the band gap energy of TiO2 (3.24 eV) to 2.57 eV, 2.47 eV and 2.28 eV. Based on XRD analysis, it is known that the Co(II)-TiO2/Ti photocatalyst has anatase phase with a crystal size of 15-17 nm. The photocatalytic activity of Co(II)-TiO2/Ti under visible light illumination was evaluated for inhibition of Escherichia coli bacterial growth. Co(II)-TiO2/Ti photocatalyst at 2.0% Co(II) concentration had the best inhibition (43.2%) compared to 0.5% and 1.0% Co(II) concentrations, respectively 18% inhibition and 27%.